Effect of Indirect Taxes on Consumer Goods Prices in Nigeria - Eke Robert, Ike; Efedhoma Excellence, Prince (INTI International University, 2025)
With an emphasis on Value Added Tax (VAT), Excise Tax (ET), and Import Tariffs (IT), this study examines how indirect taxes affect the price of consumer products in Nigeria. The survey aims at evaluating the influence of VAT rates, ET rates, and import tariffs on the prices of consumer goods in Nigeria. By analysing secondary data from government reports, industry reports, and previous studies, the research explores the extent to which these indirect taxes contribute to inflationary pressures and consumer prices in the country. Using a quantitative approach and regression analysis, the inquiry explores the interaction between tax rates and consumer prices. It concludes that there is a statistically significant positive correlation between VAT rates and the prices of consumer goods, with VAT having a greater effect than the other taxes. The effect of Excise Tax on prices is positive but weaker, while Import Tariffs also show a positive, though less pronounced, influence on prices. These findings suggest that VAT is the most significant contributor to higher consumer prices in Nigeria, while Excise Tax and Import Tariffs also contribute but to a lesser extent. The study recommends that policymakers carefully consider the impacts of indirect taxes on consumer prices and inflation when making tax policy decisions. In particular, VAT rates should be examined in relation to their impact on consumer affordability and economic stability. Further research is also recommended to determine the long-term implications of indirect taxation on the broader Nigerian economy and to explore potential strategies for mitigating negative effects on consumers.